APLIKASI MEDIA PEMBELAJARAN TULANG MANUSIA MENGGUNAKAN AUGMENTED REALITY (AR) BERBASIS ANDROID - Khemal Rizky Ramadhan; Youllia Indrawaty Nurhasanah; Rio Korio Utoro (Maranatha University Press, 2017)
Augmented Reality is a technology of combining two-dimensional virtual objects and three-dimensional virtual objects that are interactive in real-world times. Many fields have been using Augmented Reality technology, one of them in the field of education. In the field of technology education Augmented Reality serves as an interactive learning media for teaching and learning process more interesting and innovative. Augmented Reality technology is applied to the learning of human hand bone recognition. The use of Augmented Reality technology is expected to display the human handbag objects virtually in the form of three dimensions in a book that has been equipped with markers as props. Markers detected by the smartphone's camera will display 3-dimensional objects that match the detected markers. The process of making it, 3D objects created using Blender 3D and packaged by using Unity software, after the packaging process is finished then the results will be transferred to the smartphone that can be directly installed by the user. In order to facilitate the user to be able to use the application and can see how the human hand bones.Â Keywordsâ€” 3D, Augmented Reality, Human Bones, Learning, Unity,Â Smartphone.